Sosialisasi Pencegahan Bullying melalui Podcast Islami pada Remaja untuk Meningkatkan Sikap Anti-bullying - Jias Mengki; Syatria Adymas Pranajaya; Adriansyah NZ; Randi Muhammad Gumilang; M. Agus Wahyudi (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service project aims to explore the effectiveness of Islamic podcasts as a medium for bullying prevention awareness among Muslim adolescents. The Islamic podcast was selected as an educational tool to deliver messages about the dangers of bullying and preventive measures through an approach grounded in Islamic values. The program employed a digital education approach, and its effectiveness was assessed using pre- and post-intervention surveys to measure changes in adolescents’ knowledge, attitudes, and engagement after listening to the podcast. The results revealed a significant increase in adolescents’ understanding of bullying, as well as more positive attitudes toward the importance of reporting and avoiding such behavior. Moreover, active participation in interactive discussions during the podcast and engagement on social media platforms indicated that interactive elements reinforced comprehension and the overall impact of the messages. These findings suggest that Islamic podcasts are an effective tool for educating and preventing bullying among youth and may serve as a long-term strategy to foster a safer and more compassionate social environment.